Pelatihan Media Pembelajaran Multimedia Bagi Guru SD Negeri Mranggen 2 Kabupaten Demak - Mira Azizah; Prasena Arisyanto; Qoriati Mushafanah; M. Yusuf Setya Wardhana (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
Continuously developing science and technology requires teachers to innovate and increase creativity to develop learning media for students. The problem faced by teachers is that there are still teachers who have not been able to develop digital learning media, including teachers at SD Negeri Mranggen 2. The results of interviews with school principals and teachers there show that in carrying out learning not all teachers are willing and able to develop and use learning media. in the classroom. Usually only use books and worksheets. This has an impact on student learning outcomes which are not optimal. Not all of the teachers there are proficient in using applications like Canva. Based on these findings, it is necessary to carry out training to develop interactive learning media by utilizing several applications, for example Canva, Wordwall, In Video, and Capcut. Training consists of a preparation stage, implementation stage and evaluation stage. The method used at the implementation stage is delivery of material through lectures, demonstrations of the manufacturing process, and independent practice. The results obtained from PKM activities are increasing understanding of the concept of learning media, especially interactive multimedia and being able to produce media products using the Canva application.